Field notes contributed by Thomas J. Staudt, winter 1981-1982 - Staudt, Thomas J.et al (1981)
Field notes were contributed by Thomas J. Staudt and observer, James P. Sandrock. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed